2010
DOI: 10.1172/jci41366
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tribbles homolog 2–specific antibody levels in narcolepsy patients

Abstract: Narcolepsy is a sleep disorder characterized by excessive daytime sleepiness and attacks of muscle atonia triggered by strong emotions (cataplexy). Narcolepsy is caused by hypocretin (orexin) deficiency, paralleled by a dramatic loss in hypothalamic hypocretin-producing neurons. It is believed that narcolepsy is an autoimmune disorder, although definitive proof of this, such as the presence of autoantibodies, is still lacking. We engineered a transgenic mouse model to identify peptides enriched within hypocret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(195 citation statements)
references
References 29 publications
9
180
1
5
Order By: Relevance
“…Antibodies directed against several intracellular or membrane-bound neuronal autoantigens have been detected in the serum of narcolepsy patients (9)(10)(11). In particular, a recent study reported that 85% of Finnish T1N patients carrying the HLA-DQB1*06:02 allele and vaccinated with Pandemrix presented antibodies against the orexin receptor type 2.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies directed against several intracellular or membrane-bound neuronal autoantigens have been detected in the serum of narcolepsy patients (9)(10)(11). In particular, a recent study reported that 85% of Finnish T1N patients carrying the HLA-DQB1*06:02 allele and vaccinated with Pandemrix presented antibodies against the orexin receptor type 2.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the autoimmune hypothesis underlying narcolepsy, autoantibodies against Tribbles homolog 2 (TRIB2), a protein synthesized in hypocretin neurons, are evident in a proportion of patients with narcolepsy, a finding that has been replicated in three separate studies. [10][11][12] In addition, the surge of cases of narcolepsy following pandemic H1N1 infection and mass vaccination with Pandemrix (GlaxoSmithKline, Brentford, Middlesex, UK) lends further support to an autoimmune etiology, [13][14][15][16] likely due to serum antibodies to H1N1 nucleoprotein in patients with vaccine-associated narcolepsy cross-reacting with the hypocretin receptor 2 (an effect observed following Pandremix, but not Focetria [Novartis, Novartis International AG, Basel, Switzerland] vaccination). 17 However, in the absence of formal identification and detailed understanding of the mechanisms linking autoimmunity with the destruction of hypocretin neurons, no disease-modifying therapies for narcolepsy have yet been developed.…”
mentioning
confidence: 99%
“…Recently, Tribbles homolog 2 (Trib2) was reported as a candidate antigen involved in the destruction of orexin neurons (16). Trib2 was shown to be abundantly expressed in orexin neurons, and levels of Trib2-specific antibodies were much higher in patients with narcolepsy, especially shortly after the disease onset, 7 although it is still unknown if Trib2-specific antibodies are directly involved in cell death, or if the antibody production is a consequence of cell damage by other unknown mechanisms (17).…”
Section: Human Narcolepsy and Orexin Deficiencymentioning
confidence: 99%